Formation of surface nanobubbles on nanostructured substrates. Issue 3 (1st December 2016) - Wang, Lei; Wang, Xingya; Wang, Liansheng; Hu, Jun; Wang, Chun Lei; Zhao, Binyu; Zhang, Xuehua; Tai, Renzhong; He, Mengdong; Chen, Liqun; Zhang, Lijuan
Abstract : By a combination of experiments and molecular dynamics (MD) simulations, we demonstrated that the sizes and contact angles of the formed nanobubbles could be controlled by the nanostructured substrates. Abstract : The nucleation and stability of nanoscale gas bubbles located at a solid/liquid interface are attracting significant research interest. It is known that the physical and chemical properties of the solid surface are crucial for the formation and properties of the surface nanobubbles. Herein, we experimentally and numerically investigated the formation of nanobubbles on nanostructured substrates. Two kinds of nanopatterned surfaces, namely, nanotrenches and nanopores, were fabricated using an electron beam lithography technique and used as substrates for the formation of nanobubbles. Atomic force microscopy images showed that all nanobubbles were selectively located on the hydrophobic domains but not on the hydrophilic domains. The sizes and contact angles of the nanobubbles became smaller with a decrease in the size of the hydrophobic domains. The results indicated that the formation and stability of the nanobubbles could be controlled by regulating the sizes and periods of confinement of the hydrophobic nanopatterns. The experimental results were also supported by molecular dynamics simulations. The present study will be very helpful for understanding the effects of surface features on the nucleation and stability of nanobubbles/nanodroplets at a solid/liquid interface.